2001
DOI: 10.2460/ajvr.2001.62.77
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics and pharmacokinetics of ketoprofen enantiomers in sheep

Abstract: Inhibition of serum TXB2 concentration and exudate PGE2 synthesis for similar time courses after S(+) KTP administration indicates that it is a nonselective inhibitor of COX in sheep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
3
22
1
Order By: Relevance
“…The elimination half-life of ketoprofen in plasma was higher after the overdose of ketoprofen in the sheep of the present study than in sheep in other studies 25,26 after administration of a frequently used dose of racemic ketoprofen (3 mg/kg) or its enantiomers. Approximately 2 hours after administration of ketoprofen at a dose of 30 mg/kg, the plasma concentration of ketoprofen in our study was at the same value as the maximum concentration reported in sheep after administration at the frequently used dose of 3 mg/kg.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The elimination half-life of ketoprofen in plasma was higher after the overdose of ketoprofen in the sheep of the present study than in sheep in other studies 25,26 after administration of a frequently used dose of racemic ketoprofen (3 mg/kg) or its enantiomers. Approximately 2 hours after administration of ketoprofen at a dose of 30 mg/kg, the plasma concentration of ketoprofen in our study was at the same value as the maximum concentration reported in sheep after administration at the frequently used dose of 3 mg/kg.…”
Section: Discussioncontrasting
confidence: 48%
“…Approximately 2 hours after administration of ketoprofen at a dose of 30 mg/kg, the plasma concentration of ketoprofen in our study was at the same value as the maximum concentration reported in sheep after administration at the frequently used dose of 3 mg/kg. 25,26 Thus, exposure to the toxic plasma concentration of ketoprofen was probably relatively short, and most of the injuries in the tubular cells can be expected to have taken place during the early phase of our follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesized that the former was caused by R-ketoprofen and the later by S-ketoprofen. Ketoprofen concentrations persist for longer in inflammatory exudates than in plasma [15,17,28,45,46], and the clinical effect may therefore last longer than estimated from concentrations in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for the more rapid plasma clearance of S-ketoprofen observed in elephants is chiral inversion, in which S-ketoprofen is converted to the R-enantiomer. 30 Selective metabolism of S-ketoprofen to either the hydroxy ketoprofen metabolite or the glycine conjugate reported here would also result in increased Cl p for S-ketoprofen. 19 In the same study, conversion of R-ketoprofen to S-ketoprofen was also reported in mice, gerbils, guinea pigs, rabbits, and cynomolgus monkeys, but this conversion was < 50% of the total ketoprofen dose.…”
Section: Discussionmentioning
confidence: 74%
“…24 Statistical analyses-Pharmacokinetic values obtained for R-ketoprofen and S-ketoprofen following administration by either route were compared by use of Wilcoxon matchedpairs signed-rank tests. [27][28][29][30][31][32][33][34][35] A test for normality was not performed, as it is inappropriate to assume that data obtained from 5 animals are normally distributed. Values are reported as mean, median, and range.…”
Section: Oral Bioavailability and Pharmacokinetic Characteristics Of mentioning
confidence: 99%